Novel salicylanilides from 4,5-dihalogenated salicylic acids: Synthesis, antimicrobial activity and cytotoxicity - Paraskevopoulos, Georgios; Monteiro, Sara; Vosátka, Rudolf; Krátký, Martin; Navrátilová, Lucie; Trejtnar, František; Stolaříková, Jiřina; Vinšová, Jarmila (Bioorganic & medicinal chemistry, 2017)
Salicylanilides have proved their activity against tuberculosis (TB). One weak electron-withdrawing substituent is favored at the salicylic part, specially Cl or Br atoms at positions 4 or 5. On the other hand, the antimycobacterial activity of salicylanilides is negatively affected when a strong electron-withdrawing substituent (NO2) is present at the same positions. Herein we describe the synthesis and characterization of novel salicylanilides possessing two weak electron-withdrawing groups (halogen atoms) at their salicylic part and compare their antitubercular activity with their monohalogenated analogues. All dihalogenated derivatives proved to possess antitubercular activity at a very narrow micromolar range (MIC=1-4μM), similar with their most active monohalogenated analogues. More importantly, the most active final molecules were further screened against multidrug resistant strains and found to inhibit their growth at the range of 0.5-4μM.
Keywords: Tuberculosis, Multidrug-Resistant; Dose-Response Relationship, Drug; Salicylanilides; vztah mezi dávkou a účinkem léčiva; buňky Hep G2; salicylanilidy; multirezistentní tuberkulóza; Hep G2 Cells; Microbial Sensitivity Tests; Salicylates; Antitubercular Agents; vztahy mezi strukturou a aktivitou; Humans; Molecular Structure; viabilita buněk; Cell Survival; molekulární struktura; salicylany; mikrobiální testy citlivosti; Structure-Activity Relationship; Mycobacterium; lidé; antituberkulotika